Recuerdos, emoción, representación. Formas de la memoria de la represión en la España actual - Piedras Monroy, Pedro (Studia Romanica Posnaniensia, 2017)
History has got the monopoly of legitimate representation of the past, above all due to its privileged academic position. Its accounts operate as true and valid and often label all the rest as fiction. There are nevertheless some other forms, linked to memory, capable of learning from and narrating through emotions, opening paths of understanding, compromise and intervention in society. Referred to the memory of repression in Spain, we talk in this article about graphic novel, photography and documentary films.